Internet service providers liability for third party content: Freedom to operate? - Abdul Ghani Azmi, Ida Madieha; Ismail, Suzi Fadhilah; Daud, Mahyuddin (IEEE, 2017)
Internet Service Providers (ISPs) are instrumental in the smooth running of Internet service and they should enjoy some freedom to operate without unnecessary fear of being sued for the illegality of the content that flows through their network. Without such immunity, no ISPs would be willing to invest money in acquiring latest technology and protocols in the provision of their services. Generally, ISPs possess no editorial control over the online materials that passes through their services. It is therefore justified that they should neither be imposed with the legal burden to police content nor be held liable for any infringing or harmful materials posted online. In early United States (U.S.) jurisprudence, the courts have found ISPs to be liable for third party contents if they moderated or exercised some forms of editorial control over them. The U.S. Digital Millennium Copyright Act (DMCA) has managed to change the legal landscape by creating a mandatory obligation on ISPs to take down those infringing materials once the copyright holders give a notice of takedown request. In exchange, a ‘safe harbour’ privilege is assured to the ISPs so that they are exempted from liabilities that might arise from their action in complying with the takedown request. The system which was introduced and is currently in practice in the U.S. seems to garner a wide acceptance gradually and has been adopted in some other countries. In support of this contention, efforts to transpose the similar procedure transpired via negotiations and multi-lateral agreements involving a number of countries.